Effects of leaf removal on leaf gas exchange parameters of Vitis vinifera L. (Cv. Jaen) - Andrade, I. (2007)
The effects af three intensity leveis af defoliation (control non-defoliation, leaves removed up lo the third node and up to the sixth node) are compared on photos'ynthetic activity and Icave glucldes af Jaeo grapevines grown the Dão Experimental Center in Nelas (Portugal). Leaf removal produced a significanl increase af (eaf gas exchanges, photosynthetic rate and stamatal conductance af the remaining leaves but had no signiflcant effcct on water use efficiency. 'Nhen compared with controI plants, dcfoliation treatments induced a favourable effect on the leaves hexoses content. The strongest levei of defoliation induced a starch levei signifIcantly higher than the other treatments. These effects seem to have compensaled the influence of reduced leaf area on vigour~ yield components and sugar content in the must, since no significant differences were found about these last variables